The grieving process and the mental health of the nursing team in the face of death by COVID-19 (Research, Society and Development, 2022)
Among the professionals who were on the front lines of care for patients with corona virus disease, the largest contingent is nursing, since most of this work involves direct contact with infected patients. In view of all these events, it is considered that the death caused by this disease constituted a threat. The objective of this study is to report the impacts on mental health and the grieving process faced by the frontline nursing team in the fight against COVID-19, in the face of the recurrent death of patients and colleagues. This is a descriptive study, with a qualitative approach, of the experience report type, carried out in February 2021, based on a conversation circle with nurses who work in hospitals and basic health units in the city of Belém. In view of the presentations and reports of professionals during the conversation circle about the experiences in the pandemic period, there were different experiences, points raised regarding the fear of the disease, the difficulties encountered during work, the lack of materials and equipment to assist all patients and mainly about the recurrent death process and how it affected them. The pandemic refers to the fact that, as humans, we are mutually dependent on each other. No one can take care of themselves alone, they will always depend on others, especially the health team, especially Nursing, due to the greater proximity to the patient, and in the face of the large number of lives lost, the mental health of these professionals becomes even more shaken.